Acne vulgaris. Issue 11 (November 2021) - Pathak, Anjali; Dattani, Anusha
Acne vulgaris (acne) is a multi-factorial chronic inflammatory skin disease that is encountered frequently in general practice, accounting for over 3 500 000 annual consultations in the UK. It has an estimated global prevalence of 9.4%; and is often considered a teenage affliction, impacting virtually all adolescents to some extent. Nevertheless, it is surprisingly common in the adult population, affecting 8% of those aged 25–34 years and 3% of adults aged 35–44 years. This article explores key aspects of diagnosis and management, and considers specific scenarios such as pregnancy and transgender patients as well as the importance of psychosocial support and holistic care.